Foresthlon: Investigating Gender Experience Through a Hybrid BCI Game - Konečný, Roman; Liarokapis, Fotis (My University, 2021)
Foresthlon is an adaptation of the well known Biathlon game where the player has to move in a forest as well as shoot at the target in order to win the game. A two-dimensional hybrid BCI game was designed and implemented in order to provide a new and exciting experience for the player without ruining gameplay. The main goal of the game is to run and hit all the targets as quickly as possible as the main indicator of how successful the attempt is the time the player was able to finish the game. A user study was performed with 30 participants to examine gender differences in terms of user-experience, cognitive workload, and performance. Results indicate that male participants performed slightly better than females, although there are no significant differences.
Keywords: Brain-Computer Interaction; Hybrid games; User studies